OP0069 PERFORMANCE OF AMERICAN COLLEGE OF RHEUMATOLOGY (ACR) COMBINED RESPONSE INDEX IN DIFFUSE CUTANEOUS SYSTEMIC SCLEROSIS (CRISS) SCORE IN PHASE 2 TRIAL OF LENABASUM IN DIFFUSE CUTANEOUS SYSTEMIC SCLEROSIS (DCSS). (June 2019) - Spiera, Robert; Khanna, Dinesh; Dgetluck, Nancy; Conley, Brian; White, Barbara
Abstract : Background: Change in modified Rodnan skin score (mRSS) has been used as primary efficacy outcome in at least 13 failed controlled studies in dcSSc. In 2016, the CRISS score was provisionally accepted by ACR as a primary efficacy outcome for clinical trials in dcSSc. Its performance as a primary efficacy outcome has not been tested in a clinical trial. Objectives: To evaluate performance of ACR CRISS outcome measure in the lenabasum Phase 2 study in dcSSc, the first study in which it was used prospectively as the primary efficacy outcome. Methods: The Phase 2 study JBT101-SSc-001 (NCT02465437 ) included a 16-week, double-blinded, randomized, placebo-controlled Part A followed by an open-label extension (OLE). ACR CRISS score is calculated from a weighted exponential formula that includes change in mRSS, Patient Global Assessment (PtGA), HAQ-DI, Physician Global Assessment (MDGA), and FVC% predicted. Spearman correlations were determined for: pairs of core items at Baseline; change in pairs of core items; and change in a given core item and calculated ACR CRISS score. Median ACR CRISS scores were determined in subjects with different levels of improvement in patient-reported outcomes (PROs). Results: Correlations among pairs of CRISS core items at baseline and change in core items were all < 0.80 at 4 and 12 months. The strongest correlations (r ≥ 0.60, P ≤ 0.0001) for core items at baseline were between PtGA and HAQ-DI, HAQ-DI and MDGA, and PTGA and MDGA. The strongest correlations (r ≥ 0.50, P ≤ 0.001) for changes in pairs of core items were between PtGA and HAQ-DI, HAQ-DI and MDGA, and MDGA and mRSS, all others were ≤ 0.30 (Table 1 ). Correlations between change in each core item and ACR CRISS score were all statistically significant, p ≤ 0.05 at both 4 and 12 months and very strong for change in mRSS and ACR CRISS (Table 1 ). Median ACR CRISS scores increased with increasing levels of improvement in PROs that were core items (HAQ-DI and PtGA) and even PROs (PROMIS-29 domains) that were not core items. Median ACR CRISS score associated with improvement in HAQ-DI at least -0.250 points was 0.82 and associated with at least 1-point improvement in PtGA was 0.53 at 12 months. Conclusion: In the context of the lenabasum Phase 2 clinical trial, ACR CRISS core items at baseline and change in ACR core items were not redundant (r < 0.80). Change in each core item correlated with ACR CRISS score, indicating each contributed to the score at both 4 and 12 months. The 12-month median ACR CRISS score was higher in subjects with greater levels of improvement in PROs, even PRO that were not core items, showing that ACR CRISS score reflects long-term clinical benefit in how the patent feels and functions. These data provide preliminary evaluation of the ACR CRISS score as a clinical trial endpoint in dcSSc. Disclosure of Interests: Robert Spiera Grant/research support from: Roche-Genentech, GlaxoSmithKline, Bristol-Myers Squibb, Boehringer Ingelheim, Cytori, Chemocentryx, Corbux, Consultant for: Roche-Genentech, GlaxoSmithKline, CSL Behring, Sanofi Aventis, Dinesh Khanna Shareholder of: Eicos Sciences, Inc, Grant/research support from: Bayer, BMS, Pfizer, Horizon, Consultant for: Actelion Acceleron, Arena, Bayer, BI, BMS, CSL Behring, Corbus, Cytori, GSK, Genentech/Roche, Galapagos, Employee of: Elcos Sciences, Inc, Nancy Dgetluck Employee of: Corbus Pharmaceuticals, Inc., Brian Conley Employee of: Corbus Pharmaceuticals, Inc., Barbara White Shareholder of: Corbus Pharmaceuticals, Inc., Employee of: Corbus Pharmaceuticals, Inc.